2022
DOI: 10.1155/2022/5639174
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomogram for Gastrointestinal Stromal Tumors after Surgery Based on the SEER Database

Abstract: We aimed to determine prognostic factors and develop an effective and practical nomogram for predicting cancer-specific survival in gastrointestinal stromal tumor (GIST) patients. Postoperative data were obtained from the SEER database (2000-2018). Patients were divided into training and validation cohorts at random (7 : 3). Prognostic factors were screened, and a prognostic nomogram was established using log-rank testing and Cox regression. We used DCA, ROC curves, C-index, and calibration curves to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Nevertheless, previous research has indicated that the Mitotic rate did not display any significant variations in survival outcomes when undergoing multifactor feature selection. The observed disparity is incongruous with the clinical guidelines indicated earlier 7 , 8 , 10 , 11 . The veracity is found within the survival Cox nomograms, which incorporate the independent clinical factor Mitotic rate and the comprehensive index AJCC stage as simultaneous variables in the nomogram.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Nevertheless, previous research has indicated that the Mitotic rate did not display any significant variations in survival outcomes when undergoing multifactor feature selection. The observed disparity is incongruous with the clinical guidelines indicated earlier 7 , 8 , 10 , 11 . The veracity is found within the survival Cox nomograms, which incorporate the independent clinical factor Mitotic rate and the comprehensive index AJCC stage as simultaneous variables in the nomogram.…”
Section: Discussioncontrasting
confidence: 73%
“…However, the existing literature oversimplifies the treatment of missing data classified as 'unknown' in the development of nomograms. Several research 7 , 8 , 10 , 11 consider the classification of 'unknown' as a distinct category. The validity of this assumption is frequently disregarded, as it is contingent upon the proportions of categories inside the 'unknown' group being similar to the overall proportions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations